Analysis of Sustainability Management in Ho Chi Minh City - Le, Ngoc Tu; Kučera, Dušan; Kvítková, Zuzana; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis mainly analyzes, evaluates and researches to provide general results on sustainable management of Ho Chi Minh City. This is one of the most dynamic and fast-growing cities in Southeast Asia. Ho Chi Minh City is the leading city in Vietnam and is the economic, cultural, political and industrial center of the country. Over the past many years, Ho Chi Minh City has affirmed its position in the region and is constantly striving to improve. Keeping up with the world's shifting trends, the city has incorporated a sustainable development plan into its development process but continuously encounters many obstacles. The main goal of the thesis is to analyze the sustainable management situation of Ho Chi Minh City to identify challenges and directions for improvement. The analysis process is mainly through the collection of available data provided by the government such as the Ministry of Industry and Trade, the Ministry of Natural Resources and Environment Management, government administrative agencies, or other competent organizations. The theoretical contexts are based on Western academic achievements, combined with the specific situation of Ho Chi Minh City to provide proposed directions for improving sustainable management capabilities. In addition, actual surveys conducted by residents of Ho Chi Minh City were also conducted to provide a more intuitive perspective. The research results aim to provide an overview and suggest directions for building responsible, sustainable, and ethical economic spearheads in Ho Chi Minh City. Furthermore, it is expected that the research findings will raise community awareness of sustainability initiatives and offer solutions to the challenges the city is currently facing. As the trust of Vietnamese citizens in the national economy continues to erode, sustainable management serves as a guiding light for their faith and hope in the present and the future.
Vedoucí práce: Dušan Kučera
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses